Molecular investigation of Anaplasma spp. in domestic and wildlife animals in Peninsular Malaysia - Koh, Fui Xian; Panchadcharam, Chandrawathani; Sitam, Frankie Thomas; Tay, Sun Tee (Elsevier, 2018)
Anaplasma spp. are Gram-negative obligate intracellular, tick-borne bacteria which are of medical and veterinary importance. Little information is available on Anaplasma infection affecting domestic and wildlife animals in Malaysia. This study investigated the presence of Anaplasma spp. in the blood samples of domestic and wildlife animals in Peninsular Malaysia, using polymerase chain reaction (EHR-PCR) assays targeting the 16S rRNA gene of Anaplasmataceae. High detection rates (60.7% and 59.0%, respectively) of Anaplasma DNA were noted in 224 cattle (Bos taurus) and 78 deer (77 Rusa timorensis and one Rusa unicolor) investigated in this study. Of the 60 amplified fragments obtained for sequence analysis, Anaplasma marginale was exclusively detected in cattle while Anaplasma platys/Anaplasma phagocytophilum was predominantly detected in the deer. Based on sequence analyses of the longer fragment of the 16S rRNA gene (approximately 1000 bp), the occurrence of A. marginale, Anaplasma capra and Candidatus Anaplasma camelii in cattle, Candidatus A. camelii in deer and Anaplasma bovis in a goat was identified in this study. To assess whether animals were infected with more than one species of Anaplasma, nested amplification of A. phagocytophilum, A. bovis and Ehrlichia chaffeensis DNA was performed for 33 animal samples initially screened positive for Anaplasmataceae. No amplification of E. chaffeensis DNA was obtained from animals investigated. BLAST analyses of the 16S rDNA sequences from three deer (R. timorensis), a buffalo (Bubalus bubalis) and a cow (B. taurus) reveal similarity with that of Candidatus Anaplasma boleense strain (GenBank accession no.: KX987335). Sequence analyses of the partial gene fragments of major surface protein (msp4) gene from two deer (R. timorensis) and a monitor lizard (Varanus salvator) show the detection of a strain highly similar (99%) to that of A. phagocytophilum strain ZJ-China (EU008082). The findings in this study show the occurrence of various Anaplasma species including those newly reported species in Malaysian domestic and wildlife animals. The role of these animals as reservoirs/maintenance hosts for Anaplasma infection are yet to be determined.